Sphagnum-dominated bog systems are highly effective yet variable sources of bio-available iron to marine waters - Krachler, Regina; Krachler, Rudolf F.; Wallner, Gabriele; Steier, Peter; El Abiead, Yasin; Wiesinger, Hubert; Jirsa, Franz; Keppler, Bernhard K. (The Science of the total environment, 2016)
Iron is a micronutrient of particular interest as low levels of iron limit primary production of phytoplankton and carbon fluxes in extended regions of the world's oceans. Sphagnum-peatland runoff is extraordinarily rich in dissolved humic-bound iron. Given that several of the world's largest wetlands are Sphagnum-dominated peatlands, this ecosystem type may serve as one of the major sources of iron to the ocean. Here, we studied five near-coastal creeks in North Scotland using freshwater/seawater mixing experiments of natural creek water and synthetic seawater based on a 59Fe radiotracer technique combined with isotopic characterization of dissolved organic carbon by Accelerator Mass Spectrometry. Three of the creeks meander through healthy Sphagnum-dominated peat bogs and the two others through modified peatlands which have been subject to artificial drainage for centuries. The results revealed that, at the time of sampling (August 16–24, 2014), the creeks that run through modified peatlands delivered 11–15μg iron per liter creek water to seawater, whereas the creeks that run through intact peatlands delivered 350–470μg iron per liter creek water to seawater. To find out whether this humic-bound iron is bio-available to marine algae, we performed algal growth tests using the unicellular flagellated marine prymnesiophyte Diacronema lutheri and the unicellular marine green alga Chlorella salina, respectively. In both cases, the riverine humic material provided a highly bio-available source of iron to the marine algae. These results add a new item to the list of ecosystem services of Sphagnum-peatlands. [Display omitted] •We report that peat-bogs are sources of bio-available iron to marine algae.•This iron is effectively chelated with aquatic humic acids.•The radiocarbon age of the iron-carrying aquatic humic acids was up to 550years.•Analysis was focused on mixing experiments of iron-rich creek water with seawater.•Drained peatlands with low thickness of the peat strata are only weak iron sources.